Electrolyte with non-solvated liquid for cathode stability

By using liquid electrolyte composed of bis(2,2,2-trifluoroethyl) carbonate and bis(1,1-difluoroethoxy)ethane in lithium-ion batteries, the problem of the degradation of the lithium-ion battery life cycle is solved, and the stability of the cathode and anode is improved and the battery life is extended.

CN119560638APending Publication Date: 2025-03-04APPLE INC
View PDF 12 Cites 0 Cited by

Patent Information

Application Number
CN202411201653.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-09-01
Filing Date
2024-08-29
Publication Date
2025-03-04

AI Technical Summary

Technical Problem

The life cycle of lithium-ion batteries is limited by the degradation of the cathode active material and the anode active material by liquid electrolytes, and it is difficult for the prior art to develop a liquid electrolyte that can maintain the integrity of both.

Method used

A liquid electrolyte is used that contains bis(2,2,2-trifluoroethyl)carbonate (TFEC) as a diluent and bis(1,1-difluoroethoxy)ethane (BDOE) as a solvent, and in some variations are added lithium salts and additives to improve the stability of the electrolyte.

Benefits of technology

The liquid electrolyte can effectively improve the stability of the cathode and anode of the lithium-ion battery, extend the battery life, and maintain high volume energy density and long cycle life without the need for an external pressure fixture.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119560638A_ABST
    Figure CN119560638A_ABST
Patent Text Reader

Abstract

The invention discloses an electrolyte with a non-solvated liquid for cathode stability. The present disclosure relates generally to battery cells, and more particularly to liquid electrolyte solvents, diluents, and designs for lithium ion battery cells.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] priority

[0002] This patent application claims the benefit of U.S. Provisional Patent Application No. 63 / 580,251, filed on September 1, 2023, entitled “ELECTROLYTE WITH NON-SOLVATINGLIQUID FOR CATHODE STABILITY,” which is incorporated herein by reference in its entirety. Technical Field

[0003] The present disclosure relates generally to battery cells, and more particularly to electrolytes used in lithium-ion battery cells. Background Art

[0004] Lithium-ion batteries are widely used as power sources in consumer electronics. Consumer electronics require lithium-ion batteries that can deliver higher volumetric energy density and sustain more discharge-charge cycles. Lithium-ion batteries typically operate at voltages up to 4.45V (full cell voltage).

[0005] The battery life cycle can be degraded due to degradation of the cathode active material and the anode active material by the liquid electrolyte. Limited progress has been made in developing liquid electrolytes that simultaneously maintain the integrity of both the cathode active material and the anode active material. Summary of the invention

[0006] In a first aspect, the present disclosure is directed to a liquid electrolyte comprising a bis(2,2,2-trifluoroethyl) carbonate (TFEC) diluent and a bis(1,1-difluoroethoxy) ethane (BDOE) solvent. In some variations, the ratio of wt% TFEC diluent to wt% BDOE solvent may be 1:5.0-1:2.0. In some variations, the liquid electrolyte comprises a lithium salt selected from the group consisting of: LiFSI, LiTFSI, LiBOB, LiPF6, LiBF4, LiClO4, LiSO3CF3, LiN(SO2F) 2、 LiN(SO2CF3)2、LiBC4O 8、Li[PF3(C2CF5)3], LiC(SO2CF3)3 and combinations thereof. In other variations, the lithium salt is LiFSI, or a combination of LiFSI and LiBOB. In some additional variations, the amount of the lithium salt is 15 mol%-50 mol% of the liquid electrolyte. In other variations, the liquid electrolyte comprises an additive selected from the following: lithium N-methyl-N-propylpyrrolidinium bis(fluorosulfonyl)imide, difluoro(oxalate)borate (LiDFOB), prop-1-ene-1,3-sultone (PES), methylene disulfonate (MMDS), propylene carbonate (PC), vinyl ethylene carbonate (VEC), propane sultone (PS), fluoroethylene carbonate (FEC), succinonitrile (SN), ethylene carbonate (VC), adiponitrile (ADN), ethylene glycol bis(2-cyanoethyl) ether (EGPN) and combinations thereof. In some variations, the ionic liquid N-methyl-N-propylpyrrolidinium bis(fluorosulfonyl)imide is added. Each of the above additives may be selected individually or from the listed additives.

[0007] In a second aspect, the present disclosure relates to a battery cell having a cathode comprising a cathode active material disposed on a cathode current collector; and an anode comprising an anode active material disposed on an anode current collector. The anode is oriented toward the cathode so that the anode active material faces the cathode active material. A separator is disposed between the cathode active material and the anode active material. A liquid electrolyte is disposed between the cathode and the anode.

[0008] In some variations, the battery cell includes a polymer composite layer disposed between the anode and the separator. In other variations, the anode cap layer is disposed between the anode and the polymer composite layer. In still other variations, the one or more metals of the anode cap layer are Sn and Cu. The polymer composite layer can attach the anode cap layer to the separator.

[0009] The polymer composite layer may include a cross-linked polymer backbone, polyethylene glycol, polycaprolactone and a lithium salt. The cross-linked polymer backbone has an uncross-linked molecular weight between 100,000 g / mol and 2,000,000 g / mol and is selected from the group consisting of PVDF-HFP, PEGDMA, poly-DDA, PVB, PUA, PEO, PAN, PMMA and their copolymers. Polyethylene glycol may have a molecular weight between 20,000 g / mol and 200,000 g / mol and may account for between 1.0 weight % and 20.0 weight % of the polymer composite layer. Polycaprolactone may have a molecular weight between 20,000 g / mol and 200,000 g / mol and may account for between 1.0 weight % and 40.0 weight % of the polymer composite layer. In some variations, the polymer composite layer has a porosity of less than 10.0%.

[0010] In some additional variations, the ratio of lithium salt to the sum of the cross-linked polymer backbone, polyethylene glycol, and polycaprolactone is less than 0.4:1.0. In other variations, the lithium metal battery has an external operating pressure of 20 psi or less. In other variations, the cross-linked polymer backbone is PVDF-HFP. BRIEF DESCRIPTION OF THE DRAWINGS

[0011] The present disclosure will be readily understood through the following detailed description in conjunction with the accompanying drawings, in which like reference numerals represent like structural elements, and in which:

[0012] Figure 1 is a top view of a battery cell according to an exemplary embodiment; and

[0013] Figure 2 is a perspective view of a battery cell according to an exemplary embodiment;

[0014] Figure 3 is a perspective view of a battery cell according to an exemplary embodiment;

[0015] Figure 4 is a perspective view of a battery cell according to an exemplary embodiment;

[0016] Figure 5 depicts a sketch of the components of a liquid electrolyte including an inner solvation shell 502, an outer screening shell 504, according to an exemplary embodiment;

[0017] Fig. 6A and Figure 6B is a Nyquist plot depicting impedance of a battery cell having a liquid electrolyte with or without a FEC co-solvent or a BTFE diluent according to an exemplary embodiment;

[0018] Fig. 7A , Figure 7B and Figure 7C depicts a Nyquist plot containing a TFEC diluent, a TTE diluent, and a BTFE diluent according to an exemplary embodiment; and

[0019] Fig. 8A depicts capacity as a function of cycle number and resistance as a function of cycle number for a battery cell having a liquid electrolyte with a TFEC diluent and a BDOE solvent, with and without a SnCu cap and / or a polymer composite layer (PE layer) according to an exemplary embodiment; and

[0020] Figure 8B Energy and ratio as a function of cycle number are shown according to an exemplary embodiment. DETAILED DESCRIPTION

[0021] Reference will now be made in detail to the representative embodiments illustrated in the accompanying drawings. It should be understood that the following description is not intended to limit the embodiments to a preferred embodiment. On the contrary, it is intended to cover substitutions, modifications and equivalents that may be included in the essence and scope of the described embodiments defined by the appended claims.

[0022] The present disclosure relates to an electrolyte that provides low voltage stability at the anode and high voltage stability at the cathode in the presence of active lithium metal. The liquid electrolyte comprises a solvent BDOE that provides anode stability and a diluent TFEC that provides cathode stability. The battery cell also provides an anode cap layer disposed on the anode surface, and a polymer composite layer disposed on the anode cap layer. The prepared liquid electrolyte comprising a solvent and a non-solvated diluent liquid meets the stability requirements of each electrode of a lithium ion battery.

[0023]

[0024] Battery Cell

[0025] Figure 1 A top view of a battery cell 100 according to one embodiment is shown. The battery cell 100 may correspond to a lithium ion or lithium polymer battery cell for powering devices used in consumer, medical, aviation, defense, and / or transportation applications. The battery cell 100 includes a stack 102 having a plurality of layers, the plurality of layers including a cathode having a cathode active coating, a separator, and an anode having an anode active coating. More specifically, the stack 102 may include a strip of cathode active material (e.g., aluminum foil coated with a lithium compound) and a strip of anode active material (e.g., copper foil coated with carbon). The stack 102 also includes a strip of separator material (e.g., a microporous polymer film or a nonwoven fabric mat) disposed between a strip of cathode active material and a strip of anode active material. The cathode, anode, and separator layers may remain flat in a planar configuration or may be wound into a wound configuration (e.g., a "jelly roll"). An electrolyte solution is disposed between each cathode and anode.

[0026] During assembly of the battery cell 100, the stack 102 can be enclosed in a bag or container. The stack 102 can be in a planar or wound configuration, but other configurations are also possible. In some variations, the bag is such as a bag formed by folding a flexible sheet along a fold line 112. In some cases, the flexible sheet is made of aluminum with a polymer film (such as polypropylene). After folding the flexible sheet, the flexible sheet can be sealed, for example, by applying heat along the side seals 110 and along the platform seals 108. The thickness of the flexible bag can be less than or equal to 120 microns to improve the packaging efficiency of the battery cell 100, the density of the battery cell 100, or both.

[0027] The stack 102 may also include a set of conductive leads 106 coupled to the cathode and anode. The conductive leads 106 may extend through a seal in the bag (e.g., a seal formed using the sealing tape 104) to provide a terminal for the battery cell 100. The conductive leads 106 may then be used to electrically couple the battery cell 100 with one or more other battery cells to form a battery pack. For example, a battery pack may be formed by coupling battery cells in series, parallel, or a series-parallel configuration. Such coupled cells may be enclosed in a hard case to complete the battery pack, or may be embedded in a housing of a portable electronic device such as a laptop computer, tablet computer, mobile phone, personal digital assistant (PDA), digital camera, and / or portable media player.

[0028] Figure 2 A battery cell 200 (eg, Figure 1 1 . The battery includes a cathode 202 and an anode 210, wherein the cathode includes a current collector 204 and a cathode active material 206, and the anode includes an anode current collector 212 and an anode active material 214. The separator 208 is disposed between the cathode 202 and the anode 210. The liquid electrolyte 216 is disposed between the cathode 202 and the anode 210 and in contact with the separator 208. To form a battery cell, the cathode 202, the separator 208, and the anode 210 can be stacked in a planar configuration, or they can be stacked and then wound into a wound configuration. The liquid electrolyte 216 can then be added. Before assembling the battery cell, this set of layers can correspond to a unit stack.

[0029] The cathode current collector, cathode active material, anode current collector, anode active material and separator can be any material known in the art. In some variations, the cathode current collector can be aluminum foil and the anode current collector can be copper foil. The cathode active material can be any material described in, for example, 14 / 206,654, 15 / 458,604, 15 / 458,612, 15 / 709,961, 15 / 710,540, 15 / 804,186, 16 / 531,883, 16 / 529,545, 16 / 999,307, 16 / 999,328, 16 / 999,265, each of which is incorporated herein by reference in its entirety.

[0030] The salt, solvent, and non-solvated diluent prepared as a liquid electrolyte formulation can simultaneously meet the stability requirements of each electrode of a lithium metal battery design.

[0031] Figure 3A battery cell 300 is depicted that includes a lithium anode 302, a polymer composite layer 304, a porous inert separator 306, and a cathode 308. The polymer composite layer 304 is permeable to salts and solvents, but not to diluents. The polymer composite layer substantially limits the accessibility of the TFEC diluent at the anode while allowing salts, solvents, lithium, anions, and additives to reach the anode. The TFEC diluent is prevented or limited from reaching the anode surface and thereby eliminates and / or prevents the anode active material.

[0032] The ratio of wt % TFEC diluent to wt % BDOE solvent may be 1:5.0-1:2.0. The ratio may have a minimum and / or a maximum. In some variations, the ratio of wt % TFEC to wt % BDOE is at least 1:5.0. In some variations, the ratio of wt % TFEC to wt % BDOE is at least 1:4.5. In some variations, the ratio of wt % TFEC to wt % BDOE is at least 1:4.0. In some variations, the ratio of wt % TFEC to wt % BDOE is at least 1:3.5. In some variations, the ratio of wt % TFEC to wt % BDOE is at least 1:3.0. In some variations, the ratio of wt % TFEC to wt % BDOE is at least 1:2.5. In some variations, the ratio of wt % TFEC to wt % BDOE is less than or equal to 1:2.0. In some variations, the ratio of wt % TFEC to wt % BDOE is less than or equal to 1:2.5. In some variations, the ratio of wt % TFEC to wt % BDOE is less than or equal to 1:3.0. In some variations, the ratio of wt % TFEC to wt % BDOE is less than or equal to 1:3.5. In some variations, the ratio of wt % TFEC to wt % BDOE is less than or equal to 1:4.0. In some variations, the ratio of wt % TFEC to wt % BDOE is less than or equal to 1:4.5. As described herein, the amount of any upper limit may be combined with the amount of any lower limit in any combination.

[0033] The separator may include a microporous polymer film or a nonwoven fabric pad. Non-limiting examples of microporous polymer films or nonwoven fabric pads include microporous polymer films or nonwoven fabric pads of the following materials: polyethylene (PE), polypropylene (PP), polyamide (PA), polytetrafluoroethylene (PTFE), polyvinyl chloride (PVC), polyester, and polyvinylidene fluoride (PVdF). However, other microporous polymer films or nonwoven fabric pads are also possible (e.g., gel polymer electrolytes).

[0034] Generally speaking, a separator refers to a structure in a battery, such as an intercalation layer, that prevents physical contact between the cathode and the anode while allowing ions to be transported between the two. The separator is formed of a material having pores that provide ion transport channels, which may include absorbing a liquid electrolyte containing ions. The material used for the separator can be selected based on chemical stability, porosity, pore size, permeability, wettability, mechanical strength, dimensional stability, softening temperature, and thermal shrinkage. These parameters may affect battery performance and safety during operation.

[0035] Generally speaking, the liquid electrolyte can serve as a conductive path for transferring cations from the negative electrode to the positive electrode during discharge.The liquid electrolyte comprises an electrolyte salt, an electrolyte solvent, and one or more electrolyte additives.

[0036] Polymer composite layer and anode cap

[0037] For example, polymer composite layers as described herein are disclosed in US Patent Application No. 18 / 226,813, which is incorporated herein by reference in its entirety.

[0038] The polymer composite layer disclosed herein has improved pore control, ionic conductivity and membrane bonding strength when compared to known protective layers. The polymer composite layer disclosed herein has low stiffness, moderate tensile strength and sufficient elongation to provide the necessary mechanical strength, such as the ability to bend without breaking and the ability to absorb impact energy.

[0039] The electrochemical cell disclosed herein achieves high volumetric energy density and gravimetric energy density using a well-bonded layer stack, which includes an anode current collector, a lithium metal anode, an anode cap layer, a polymer composite layer, and a separator. A specific layer sequence of lithium metal in the form of a lithium metal anode covered with an anode cap layer and protected from liquid electrolyte by a polymer composite layer achieves dense and uniform lithium plating between the anode current collector and the anode cap layer, thereby creating a chemically protected environment without liquid electrolyte during cell cycling. The specific layers and sequences of layers avoid low-density lithium plating, thereby achieving and maintaining high volumetric energy density and long cycle life, all without the need for an external pressure fixture.

[0040] Relative to Figure 4 The electrochemical cell 400 disclosed herein provides a solution to the problems discussed herein by using a lithium metal anode that is spatially and therefore chemically separated from a liquid electrolyte via an intervening combination of an anode cap layer 406 and a polymer composite layer 408, wherein the anode cap layer 406 is in direct contact with the lithium metal anode 404 and the polymer composite layer 408 is in direct contact with the liquid electrolyte 416, as Figure 1. The polymer composite layer 408 absorbs lithium salts and solvent molecules from the liquid electrolyte 416 during cycling to convert the manufactured polymer composite layer 408 into a polymer electrolyte layer, while limiting the interaction between the lithium metal anode 404 and the solvent and promoting a uniform interface at the anode cap layer 406. The electrochemical cell 400 disclosed herein provides low impedance and uniform bonding interfaces. These bonding interfaces avoid the liquid electrolyte from pooling at the interface with the lithium metal anode, thereby preventing the uncontrolled growth of low-density, high-volume, dendritic, fluffy lithium metal morphology into the liquid electrolyte space.

[0041] Anode cap layer 406 comprises one or more metals, at least one of which alloys with the lithium metal of anode 404. In various aspects, anode cap layer 406 may be 0.01 μm to 10 μm thick, and in particular 0.2 μm to 3.0 μm thick, and is composed of the maximum lithiated alloy of a given metal M that is capable of forming an intermetallic compound with lithium. M may include one or more metal elements (ternary, quaternary, pentad, etc.) and may be selected from Sn, Sb, Si, Au, Zn, Al, and Mg, as non-limiting examples. M may also contain elements, such as Cu, Ti, and Ni, which will only form solid solutions with lithium in the case of being binary.

[0042] LiSn is a non-limiting example of an anode cap layer. Galvanic cells are formed when lithium and tin come into contact, which drives alloy formation to a stable state at low temperatures. LiSn also diffuses lithium ions very quickly. LiSn has a thermal conductivity of about 10-7 cm 2 / s, while LiPON and LiCoO2 have diffusion coefficients of 10-9cm 2 / s and 10-10cm 2 / s diffusion coefficient. Both lithium and tin are active materials. Adding an inactive matrix such as Cu, Ti, Ni or NiTi can provide additional stability because these components will not react or move within the layer. Non-limiting examples of anode cap layers include LiSnCu, LiSnTi, LiSnNi and LiSnNiTi. These layer compositions can be formulated so that, for example, the LiSnCu layer can be Cu-rich, or the LiSnCu layer can be coated with a Cu skin near the polymer composite layer 408. Similarly, the LiSnNiTi layer can be, for example, Ni-rich or Ti-rich, or can be coated with a Ni, Ti or NiTi skin near the polymer composite layer 408.

[0043] The anode cap layer is in contact with an excess of lithium metal in the form of a lithium metal anode, and thus adopts the maximum possible lithiated alloy during a given battery cell life. It is empirically found that when the battery cell is charged, lithium atoms are densely and uniformly plated between the anode cap layer 406 and the existing lithium metal with very low impedance, while fusing with the existing lithium metal seed. This location of lithium plating is desirable. The reason why lithium atoms are preferably plated between the anode cap layer and the lithium metal anode, rather than between the anode cap layer and the polymer composite layer, is rooted in the thermodynamic voltage gradient, which does not disappear until the incoming lithium atoms reach the lithium metal anode body. During discharge, the plated lithium is uniformly stripped. The polymer composite layer can be used in an electrochemical cell without an anode cap layer, where the polymer composite layer laminates the separator to the lithium metal or the anode current collector. However, the inventors have found that the anode cap layer enables a flatter and denser plating of lithium metal.

[0044] The anode capping layer may be formed by, for example, vapor deposition of M onto a lithium metal anode in an in-situ reaction layer, followed by controlled surface passivation with, for example, CO2 gas or a mixture thereof or an ex-situ impregnation solution containing a dilute carboxylic acid in a hydrocarbon. There are other methods for forming the anode capping layer, such as, for example, (i) dip coating the lithium metal anode into a solution containing a salt of M, with the lithium metal anode seed reacting with the salt containing M to form Li x M, or (ii) providing a salt of M as an additive in the polymer composite layer, wherein when the polymer composite layer slurry is applied to the lithium metal anode, the lithium metal anode reacts in situ at its surface to form Li x M.

[0045] The polymer composite layer 408 has a cross-linked polymer backbone, polyethylene glycol (PEG), polycaprolactone (PCL), and at least one lithium salt. These can be the only components of the polymer composite layer 408 manufactured. It is expected that additional components may be included, but they are not required. Note that during charging and discharging of the battery cell, the polymer composite layer can absorb lithium salts and limited amounts of solvent from the liquid electrolyte 416, while limiting the interaction between the anode and the solvent and promoting a uniform interface at the anode cap layer 406. Except for the casting solvent that evaporates from the manufactured polymer composite layer and is not retained therein, no ionic liquid or other solvent is used or retained in the manufactured polymer composite layer. The thickness of the polymer composite layer 408 may be between about 0.01 μm and 5.0 μm, and more specifically, the thickness is about 1.5 μm to 3.0 μm.

[0046] The cross-linked polymer backbone is a cross-linked polymer having an uncross-linked molecular weight between 100,000 g / mol and 2,000,000 g / mol and accounts for between 40.0 wt % and 90.0 wt % of the manufactured polymer composite layer 408. All ranges herein are inclusive. The polymer backbone is a metal-stable polymer with lithium metal and the anode cap layer and is elastic to dissolution with minimal swelling in the liquid electrolyte 416. The polymer backbone provides a structural matrix to accommodate PEG and PCL and provides bonding (lamination) between the separator and the anode. The polymer of the polymer backbone can be poly(vinylidene fluoride)-co-hexafluoropropylene (PVDF-HFP), poly(vinylidene fluoride) (PVDF), polyethylene glycol dimethacrylate (PEGDMA), polydiallyldimethylammonium bis(fluorosulfonyl)imide (polyDDA FSI), polyvinyl butyral (PVB), poly(urethane acrylate) (PUA), polyethylene glycol (PEO), polyacrylonitrile (PAN), poly(methyl methacrylate) (PMMA) or copolymers thereof. The cross-linked polymer backbone can be one polymer or can be a mixture of more than one polymer. The polymer backbone can be in the form of complete or partial cross-linking, and the cross-linking within the backbone can be achieved by both chemical cross-linking (during synthesis) and physical cross-linking (such as coordination of dissociated lithium salts with fluorine atoms of the polymer).

[0047] PEG has a molecular weight between 20,000 g / mol and 200,000 g / mol and accounts for between 1.0 wt % and 20.0 wt % of the manufactured polymer composite layer 408. PCL has a molecular weight between 20,000 g / mol and 200,000 g / mol and accounts for between 1.0 wt % and 40.0 wt % of the manufactured polymer composite layer 408. Both PEG and PCL can be linear or branched with 3, 4, 6 or 8 arms. The molecular weight range provides a suitable window to enable PEG and PCL to plasticize but not dissolve in the presence of liquid electrolyte 416. The ratio of PCL to PEG in the polymer composite layer is 1:1 to 3:1. The addition of PEG and PCL creates free volume for the lithium salt and a limited amount of solvent from the liquid electrolyte, making lithium salt dissociation and lithium ion conductivity possible, providing additional structural support to the polymer composite layer, and providing additional bonding to the anode and separator.

[0048] Lithium salts

[0049] The lithium salt may be any lithium salt known in the art. As a non-limiting example, the lithium salt may be one or more of lithium bis(fluorosulfonyl)imide (LiFSI), lithium bis(trifluoromethylsulfonyl)imide (LiTFSI), lithium bis(oxalate)borate (LiBOB), lithium hexafluorophosphate (LiPF6), lithium tetrafluoroborate (LiBF4), lithium perchlorate (LiClO4), LiSO3CF3, LiN(SO2F)2, LiN(SO2CF3)2, LiBC4O8, Li[PF3(C2CF5)3], and LiC(SO2CF3)3. As another non-limiting example, a dual salt system such as LiFSI and LiBOB may be used. Adding a lithium salt to the polymer composite layer 408 may improve ionic conductivity and low temperature performance. LiBOB may passivate the aluminum cathode current collector to inhibit SFI-Al corrosion.

[0050] In various aspects, the lithium salt may be 15 mol%-50 mol% in the liquid electrolyte. The salt may have a lower limit and / or upper limit of mol% of any combination described herein. In some variations, the lithium salt may account for at least 15 mol% of the liquid electrolyte. In some variations, the lithium salt may account for at least 20 mol% of the liquid electrolyte. In some variations, the lithium salt may account for at least 25 mol% of the liquid electrolyte. In some variations, the lithium salt may account for at least 30 mol% of the liquid electrolyte. In some variations, the lithium salt may account for at least 35 mol% of the liquid electrolyte. In some variations, the lithium salt may account for at least 40 mol% of the liquid electrolyte. In some variations, the lithium salt may account for at least 45 mol% of the liquid electrolyte. In some variations, the lithium salt may be less than or equal to 50 mol% of the liquid electrolyte. In some variations, the lithium salt may be less than or equal to 45 mol% of the liquid electrolyte. In some variations, the lithium salt may be less than or equal to 40 mol% of the liquid electrolyte. In some variations, the lithium salt may be less than or equal to 35 mol% of the liquid electrolyte. In some variations, the lithium salt may be less than or equal to 30 mol % of the liquid electrolyte. In some variations, the lithium salt may be less than or equal to 25 mol % of the liquid electrolyte. In some variations, the lithium salt may be less than or equal to 20 mol % of the liquid electrolyte.

[0051] Lithium salts are necessary for ion conduction. However, known polymer electrolytes may rely solely on salts for ion conduction and are gated due to the need for large amounts of lithium salts and their inherent pore-forming effects. Higher porosity (20% or greater) and larger pores (maximum pore size of 2 μm or greater) in polymer electrolyte membranes are undesirable because they allow the liquid electrolyte to react with the underlying lithium metal anode. The mechanism for generating large pores is the use of high concentrations of salts and casting solvents. During membrane processing, the solvent evaporates, leaving behind pores filled with salt. To address this issue, additional means of lithium ion conduction independent of lithium salts are sought.

[0052] The addition of PEG enhances ionic conductivity in the polymer composite layer 408. However, the use of PEG alone provides a dense polymer film with no visible pores. Figure 2 : is a SEM / EDS image of the surface of a polymer backbone (PVDF-HFP used here) with a molecular weight of 40,000 g / mol 8-arm PEG, showing no visible pores. Without the introduction of some lithium salt, the ionic conductivity is insufficient, and the lack of porosity only enables the addition of very small amounts (less than 5.0 wt%) of lithium salt before uneven, undesirable porosity occurs.

[0053] When combined with the polymer backbone, PCL has pore-forming properties. Compared with the case of adding lithium salts to form pores, PCL forms smaller (less than or equal to 1.0 μm maximum diameter), more uniform pores. Figure 3 is a SEM / EDS image of the surface of a polymer backbone (PVDF-HFP used herein) with a molecular weight of 80,000 g / mol PCL, showing small, uniform pores. PCL and PEG are blended to produce small, uniform pores filled with ion-conductive PEG. With PCL as a pore former and PEG as a pore filler, changing the ratio of PEG and PCL in the polymer composite layer can adjust the porosity of the polymer composite layer. The desired porosity is sufficient to provide the necessary ionic conductivity, but as low as possible to limit the collection of liquid electrolyte solvents. The polymer composite layer 408 disclosed herein has a porosity between 1.0 wt % and 10.0 wt %, more particularly between 1.0 wt % and 8.0 wt %, and more particularly between 1.0 wt % and 5.0 wt %.

[0054] In the case of using PEG for ionic conductivity, the amount of lithium salt required to achieve overall ionic conductivity in the polymer composite layer can be reduced. For example, the ratio of lithium salt to the sum of the cross-linked polymer backbone, PEG and PCL is less than 0.4:1.0, and more particularly 0.2:1, compared to a ratio of lithium salt to polymer of 1.1:1.0 in known polymer electrolyte layers. Figure 4 and Figure 5 are SEM / EDS images illustrating the effect of increasing lithium salt concentration on pore size and uniformity. Figure 4 and Figure 5is an image of the surface of the polymer composite layer before bonding to the separator. The polymer composite layer has a total of 20 weight percent PEG and PCL and 80 weight percent PVDF-HFP, and the ratio of PCL to PEG is 3:1. In some variations, the lithium salt accounts for 17.0 weight percent of the polymer composite layer, resulting in a porosity of 8.0%, while in other variations, the lithium salt accounts for 34.0 weight percent of the polymer composite layer, resulting in a porosity of 19.0%. In cases where both PEG and the lithium salt contribute to ionic conductivity, the lower concentration of the lithium salt achieves an ionic conductivity greater than or equal to 0.6×10-4 S / cm -1 The polymer composite layer 408 is provided. The polymer composite layer acts as a protective layer to block the contact between the liquid electrolyte and the lithium metal anode, thereby reducing or preventing the continuous reaction between the electrolyte and the lithium metal. The polymer composite layer is used as an additional electrolyte layer because the polymer composite layer is lithium ion conductive, thereby promoting uniform lithium distribution and plating at the electrode interface.

[0055] The combination of PEG and PCL has an additional synergistic effect. PEG is more polar than PCL, allowing the polarity of the polymer composite layer to be tuned by varying the ratio of PEG to PCL.

[0056] PCL does not form a separate melting peak / crystalline phase and will be integrated with the polymer backbone and lithium salt system. PEG forms a separate crystalline phase because its polarity is significantly different from the polymer backbone. The blending of PEG and PCL reduces the crystallinity of PEG, thereby enhancing the mobility of the polymer chain and improving the room temperature conductivity of the polymer composite layer. See the chart in Figure 6, which illustrates the crystallinity of PEG, PCL, a mixture of PEG and PCL, and no PEG or PCL. The higher the melting enthalpy, the greater the crystallinity. Crystallinity makes the material strong, but also makes it brittle. The polymer composite layer disclosed herein has the ability to bend without breaking and absorb impact energy.

[0057] The blending of PEG and PCL reduces stiffness, provides moderate tensile strength and longer elongation, and makes the polymer composite layer highly elastic. When the material has higher stiffness, it is harder and has less adhesion. It also lacks the flexibility to adapt to the roughness of the lithium surface. The polymer composite layer disclosed herein has lower stiffness, moderate tensile strength and longer elongation, thereby providing an excellent bonding material to attach the separator to the anode.

[0058] The polymer composite layer is used to laminate or bond the anode (whether it is the anode cap layer or lithium metal) to the separator, thereby providing strong adhesion between the layers. The internal pressure provided by bonding to the lithium metal is conducive to dense lithium plating under low or no external pressure. The combination of the polymer backbone, PEG and PCL provides excellent bonding strength between the anode and the separator, with a peel strength of more than 60N / m and even a peel strength of 70N / m using a 7-day LE immersion test of the anode, polymer composite layer and separator. In order to achieve this strong bond, the polymer composite layer slurry is cast onto the anode cap layer (or cast onto the lithium metal of the anode if there is no cap layer) before the separator is placed in the slurry before the slurry is dried. The resulting bonding strength is a function of the polymer composite layer, the casting solvent and the drying conditions after casting. The casting solvent may be dimethylacetamide (DMAc), dimethylformamide (DMF), N-methyl-2-pyrrolidone (NMP), tetramethylurea (TMU), N,N-diethylacetamide (DEAc), triethyl phosphate (TEP), and mixtures thereof. The casting solvent is not part of the polymer composite layer or electrochemical cell being manufactured.

[0059] The combination of the strong bonding of the separator to the anode and the reduced porosity of the polymer composite layer enables the use of a separator with increased porosity. A separator with a porosity of 60% or more can be used, compared to conventional separator porosities of 40% or less, which reduces internal battery cell resistance. The increased separator porosity also improves the elastic properties of the separator and the layers to which it is bonded, which better accommodates the non-uniformity of lithium plating.

[0060] The polymer composite layer 408 disclosed herein reduces uneven and fluffy lithium plating while reducing or eliminating the external operating pressure requirements for the battery, resulting in stable battery cell performance. The electrochemical battery cell stack design with a polymer composite layer that bonds the separator to the anode allows cycling at 0 psi external operating pressure and C / 3 charging rate. More than 240 cycles are achieved at a discharge capacity greater than 80%, an increase of 60% over conventional lithium battery cell designs.

[0061] Two embodiments of polymer composite layer 408 made as disclosed herein are provided in the table below.

[0062]

[0063]

[0064] Without wishing to be bound by any particular theory or mode of action, Figure 5A sketch of the components of a liquid electrolyte is depicted. Salt and additive system 500 includes an inner solvation shell 502, an outer screening shell 504. The inner solvation shell 502 contains lithium ions 506, anions 508, ionic additives 510, and solvent 512. The outer screening shell 504 contains a screening diluent 514. During operation of the battery cell, the outer screening shell 504 containing the diluent 514 can restrict the access of the TFEC. The diluent cannot dissolve the salt, so it does not participate in the inner solvation shell. The lithium ions 506, anions 508, ionic additives 510, and solvent 512 cannot enter the cathode. The diluent reaches the cathode before the lithium ions in the inner shell. At the cathode end, the TFEC provides a screening effect.

[0065] Again, without wishing to be bound by any particular theory or mode of action, the TFEC diluent is in the outer solvation shell / sphere of the dissolved Li ions in solution. The TFEC diluent occupies the outer solvation shell due to weak salt interactions, surrounding the salt and solvent components that occupy the inner solvation shell (there are strong interactions between the salt and solvent). The TFEC diluent molecules can screen the reactivity of the salt and solvent components at the cathode. The TFEC diluent has limited affinity for the permeating polymer composite layer and is retained in the compartment facing the cathode.

[0066] TFEC diluents can reduce the overall cell impedance when using reactive electrolyte formulations. By enabling diluent screening, impedance can be used to describe the reduction of reactivity from >1000Ω to a more typical <5Ω.

[0067] Fig. 6A and Figure 6B is a Nyquist plot depicting the impedance of a battery cell having a liquid electrolyte comprising LiFSI+P13FSI+DMAc, with or without FEC co-solvent or BTFE diluent. Fig. 6A yes Figure 6B Zoomed image of .

[0068] like Figure 6B As shown, the reactivity of the components with lithium, liquid electrolyte without FEC shows an impedance of 200 ohms. However, the impedance of the battery cell containing FEC co-solvent shows screening of the solvent, thereby reducing the interaction of the components with the anode or cathode. Figure 6B of Fig. 6A In the zoomed image, the reactivity of the solvent is significantly reduced when the BTFE diluent is added. With the BTFE diluent, the diluent shows only a few ohms of interfacial impedance. The ability of the diluent to screen the reactivity of bare lithium metal. The BTFE diluent provides stability to both the cathode and the anode.

[0069] Fig. 7A , Figure 7B and Figure 7CThe Nyquist plots for TFEC diluent, TTE diluent, and BTFE diluent are depicted. The impedance across each cell is observed when the cell is charged. In the uncharged state, a large tail is observed for each diluent. Fig. 7A As shown in the TFEC diluent, the anode interface showed minimal growth. Figure 7B As shown in Figure 2, the anode interface grows more than the TFEC. Figure 7C As shown, the BTFE diluent showed significantly more anodic growth.

[0070] Fig. 8A Capacity as a function of cycle number and resistance as a function of cycle number are plotted for battery cells with liquid electrolyte containing TFEC diluent and BDOE solvent, with and without SnCu cap and / or polymer composite layer (PE layer). Figure 8B Energy and ratio as a function of cycle number are shown. The bare lithium anode exposed to a liquid electrolyte containing TFEC shows a transient drop in direct current internal resistance (DCIR) and coulombic efficiency (CE), as well as a collapsed anode interface. These data all indicate a failed anode. The introduction of the LiCuSn cap layer delayed the onset of anode failure, however, by cycle 12, the DCIR peaked and the CE began to drop, indicating lithium overplating. In contrast, the battery cell with the polymer composite layer had a stable DCIR by cycle 30. The anode interface and CE indicate that the anode has not degraded and is functioning properly.

[0071] additive

[0072] In some variations, the liquid electrolyte may include one or more additives. In various aspects, the additives may include any combination and quantity range of the following: N-methyl-N-propylpyrrolidinium bis(fluorosulfonyl)imide, lithium difluoro(oxalate)borate (LiDFOB), prop-1-ene-1,3-sultone (PES), methylene disulfonate (MMDS), vinyl ethylene carbonate (VEC), propane sultone (PS), fluoroethylene carbonate (FEC), succinonitrile (SN), ethylene carbonate (VC), adiponitrile (ADN), ethylene glycol bis(2-cyanoethyl) ether (EGPN) and / or 1,3,6-hexanetrinitrile (HTCN). In some variations, an ionic liquid N-methyl-N-propylpyrrolidinium bis(fluorosulfonyl)imide is added. Each of the above additives may be selected individually or selected from the listed additives.

[0073] In some variations, LiDFOB is at least 0.1 wt % of the total liquid electrolyte. In some variations, LiDFOB is at least 0.2 wt % of the total liquid electrolyte. In some variations, LiDFOB is at least 0.3 wt % of the total liquid electrolyte. In some variations, LiDFOB is at least 0.4 wt % of the total liquid electrolyte. In some variations, LiDFOB is at least 0.5 wt % of the total liquid electrolyte. In some variations, LiDFOB is at least 0.6 wt % of the total liquid electrolyte. In some variations, LiDFOB is at least 0.7 wt % of the total liquid electrolyte. In some variations, LiDFOB is at least 0.8 wt % of the total liquid electrolyte. In some variations, LiDFOB is at least 0.9 wt % of the total liquid electrolyte. In some variations, LiDFOB is at least 1.0 wt % of the total liquid electrolyte. In some variations, LiDFOB is at least 1.3 wt % of the total liquid electrolyte. In some variations, LiDFOB is at least 1.6 wt % of the total liquid electrolyte. In some variations, LiDFOB is at least 1.9 wt % of the total liquid electrolyte.

[0074] In some variations, LiDFOB is less than or equal to 2.0 wt % of the total liquid electrolyte. In some variations, LiDFOB is less than or equal to 1.9 wt % of the total liquid electrolyte. In some variations, LiDFOB is less than or equal to 1.3 wt % of the total liquid electrolyte. In some variations, LiDFOB is less than or equal to 1.3 wt % of the total liquid electrolyte. In some variations, LiDFOB is less than or equal to 1.1 wt % of the total liquid electrolyte. In some variations, LiDFOB is less than or equal to 1.0 wt % of the total liquid electrolyte. In some variations, LiDFOB is less than or equal to 0.9 wt % of the total liquid electrolyte. In some variations, LiDFOB is less than or equal to 0.8 wt % of the total liquid electrolyte. In some variations, LiDFOB is less than or equal to 0.7 wt % of the total liquid electrolyte. In some variations, LiDFOB is less than or equal to 0.6 wt % of the total liquid electrolyte. In some variations, LiDFOB is less than or equal to 0.5 wt % of the total liquid electrolyte. In some variations, LiDFOB is less than or equal to 0.4 wt % of the total liquid electrolyte. In some variations, LiDFOB is less than or equal to 0.3 wt % of the total liquid electrolyte. In some variations, LiDFOB is less than or equal to 0.2 wt % of the total liquid electrolyte.

[0075] In some variations, the amount of PES is at least 0.5 wt % of the total liquid electrolyte. In some variations, the amount of PES is at least 0.6 wt % of the total liquid electrolyte. In some variations, the amount of PES is at least 0.9 wt % of the total liquid electrolyte. In some variations, the amount of PES is at least 1.3 wt % of the total liquid electrolyte. In some variations, the amount of PES is at least 1.6 wt % of the total liquid electrolyte. In some variations, the amount of PES is at least 1.9 wt % of the total liquid electrolyte. In some variations, the amount of PES is at least 2.2 wt % of the total liquid electrolyte. In some variations, the amount of PES is at least 2.5 wt % of the total liquid electrolyte. In some variations, the amount of PES is at least 2.8 wt % of the total liquid electrolyte. In some variations, the amount of PES is at least 3.1 wt % of the total liquid electrolyte.

[0076] In some variations, the amount of PES is less than or equal to 3.5 wt % of the total liquid electrolyte. In some variations, the amount of PES is less than or equal to 3.1 wt % of the total liquid electrolyte. In some variations, the amount of PES is less than or equal to 2.8 wt % of the total liquid electrolyte. In some variations, the amount of PES is less than or equal to 2.5 wt % of the total liquid electrolyte. In some variations, the amount of PES is less than or equal to 2.2 wt % of the total liquid electrolyte. In some variations, the amount of PES is less than or equal to 1.9 wt % of the total liquid electrolyte. In some variations, the amount of PES is less than or equal to 1.6 wt % of the total liquid electrolyte. In some variations, the amount of PES is less than or equal to 1.3 wt % of the total liquid electrolyte. In some variations, the amount of PES is less than or equal to 1.1 wt % of the total liquid electrolyte. In some variations, the amount of PES is less than or equal to 0.9 wt % of the total liquid electrolyte. In some variations, the amount of PES is less than or equal to 0.6 wt % of the total liquid electrolyte.

[0077] In some variations, the amount of MMDS is at least 0.1% by weight of the total liquid electrolyte. In some variations, the amount of MMDS is at least 0.2% by weight of the total liquid electrolyte. In some variations, the amount of MMDS is at least 0.3% by weight of the total liquid electrolyte. In some variations, the amount of MMDS is at least 0.4% by weight of the total liquid electrolyte. In some variations, the amount of MMDS is at least 0.5% by weight of the total liquid electrolyte. In some variations, the amount of MMDS is at least 0.6% by weight of the total liquid electrolyte. In some variations, the amount of MMDS is at least 0.7% by weight of the total liquid electrolyte. In some variations, the amount of MMDS is at least 0.8% by weight of the total liquid electrolyte. In some variations, the amount of MMDS is at least 0.9% by weight of the total liquid electrolyte. In some variations, the amount of MMDS is at least 1.0% by weight of the total liquid electrolyte. In some variations, the amount of MMDS is at least 1.1% by weight of the total liquid electrolyte. In some variations, the amount of MMDS is at least 1.2 wt % of the total liquid electrolyte. In some variations, the amount of MMDS is at least 1.3 wt % of the total liquid electrolyte. In some variations, the amount of MMDS is at least 1.4 wt % of the total liquid electrolyte.

[0078] In some variations, the amount of MMDS is less than or equal to 1.5% by weight of the total liquid electrolyte. In some variations, the amount of MMDS is less than or equal to 1.4% by weight of the total liquid electrolyte. In some variations, the amount of MMDS is less than or equal to 1.3% by weight of the total liquid electrolyte. In some variations, the amount of MMDS is less than or equal to 1.2% by weight of the total liquid electrolyte. In some variations, the amount of MMDS is less than or equal to 1.1% by weight of the total liquid electrolyte. In some variations, the amount of MMDS is less than or equal to 1.0% by weight of the total liquid electrolyte. In some variations, the amount of MMDS is less than or equal to 0.9% by weight of the total liquid electrolyte. In some variations, the amount of MMDS is less than or equal to 0.8% by weight of the total liquid electrolyte. In some variations, the amount of MMDS is less than or equal to 0.7% by weight of the total liquid electrolyte. In some variations, the amount of MMDS is less than or equal to 0.6% by weight of the total liquid electrolyte. In some variations, the amount of MMDS is less than or equal to 0.5% by weight of the total liquid electrolyte. In some variations, the amount of MMDS is less than or equal to 0.4 wt % of the total liquid electrolyte. In some variations, the amount of MMDS is less than or equal to 0.3 wt % of the total liquid electrolyte. In some variations, the amount of MMDS is less than or equal to 0.2 wt % of the total liquid electrolyte.

[0079] In some variations, the amount of VEC is at least 0.1 wt % of the total liquid electrolyte. In some variations, the amount of VEC is at least 0.2 wt % of the total liquid electrolyte. In some variations, the amount of VEC is at least 0.3 wt % of the total liquid electrolyte. In some variations, the amount of VEC is at least 0.4 wt % of the total liquid electrolyte. In some variations, the amount of VEC is at least 0.5 wt % of the total liquid electrolyte. In some variations, the amount of VEC is at least 0.6 wt % of the total liquid electrolyte. In some variations, the amount of VEC is at least 0.7 wt % of the total liquid electrolyte. In some variations, the amount of VEC is at least 0.8 wt % of the total liquid electrolyte. In some variations, the amount of VEC is at least 0.9 wt % of the total liquid electrolyte.

[0080] In some variations, the amount of VEC is less than or equal to 0.9 wt % of the total liquid electrolyte. In some variations, the amount of VEC is less than or equal to 0.8 wt % of the total liquid electrolyte. In some variations, the amount of VEC is less than or equal to 0.7 wt % of the total liquid electrolyte. In some variations, the amount of VEC is less than or equal to 0.6 wt % of the total liquid electrolyte. In some variations, the amount of VEC is less than or equal to 0.5 wt % of the total liquid electrolyte. In some variations, the amount of VEC is less than or equal to 0.4 wt % of the total liquid electrolyte. In some variations, the amount of VEC is less than or equal to 0.3 wt % of the total liquid electrolyte. In some variations, the amount of VEC is less than or equal to 0.2 wt % of the total liquid electrolyte.

[0081] In some variations, the amount of FEC is at least 2 wt % of the total liquid electrolyte. In some variations, the amount of FEC is at least 4 wt % of the total liquid electrolyte. In some variations, the amount of FEC is at least 6 wt % of the total liquid electrolyte. In some variations, the amount of FEC is at least 8 wt % of the total liquid electrolyte. In some variations, the amount of FEC is less than or equal to 10 wt % of the total liquid electrolyte. In some variations, the amount of FEC is less than or equal to 8 wt % of the total liquid electrolyte. In some variations, the amount of FEC is less than or equal to 6 wt % of the total liquid electrolyte. In some variations, the amount of FEC is less than or equal to 4 wt % of the total liquid electrolyte.

[0082] In some variations, the amount of PS is at least 0.5 wt % of the total liquid electrolyte. In some variations, the amount of PS is at least 1.0 wt % of the total liquid electrolyte. In some variations, the amount of PS is at least 1.5 wt % of the total liquid electrolyte. In some variations, the amount of PS is at least 2.0 wt % of the total liquid electrolyte. In some variations, the amount of PS is at least 2.5 wt % of the total liquid electrolyte. In some variations, the amount of PS is at least 3.0 wt % of the total liquid electrolyte. In some variations, the amount of PS is at least 3.5 wt % of the total liquid electrolyte. In some variations, the amount of PS is at least 4.0 wt % of the total liquid electrolyte. In some variations, the amount of PS is at least 4.5 wt % of the total liquid electrolyte. In some variations, the amount of PS is at least 5.0 wt % of the total liquid electrolyte.

[0083] In some variations, the amount of PS is less than or equal to 6.0 wt % of the total liquid electrolyte. In some variations, the amount of PS is less than or equal to 5.5 wt % of the total liquid electrolyte. In some variations, the amount of PS is less than or equal to 5.0 wt % of the total liquid electrolyte. In some variations, the amount of PS is less than or equal to 4.5 wt % of the total liquid electrolyte. In some variations, the amount of PS is less than or equal to 4.0 wt % of the total liquid electrolyte. In some variations, the amount of PS is less than or equal to 3.5 wt % of the total liquid electrolyte. In some variations, the amount of PS is less than or equal to 3.0 wt % of the total liquid electrolyte. In some variations, the amount of PS is less than or equal to 2.5 wt % of the total liquid electrolyte. In some variations, the amount of PS is less than or equal to 2.0 wt % of the total liquid electrolyte. In some variations, the amount of PS is less than or equal to 1.5 wt % of the total liquid electrolyte. In some variations, the amount of PS is less than or equal to 1.0 wt % of the total liquid electrolyte.

[0084] In some variations, the amount of SN is at least 0.5 wt % of the total liquid electrolyte. In some variations, the amount of SN is at least 1.0 wt % of the total liquid electrolyte. In some variations, the amount of SN is at least 1.5 wt % of the total liquid electrolyte. In some variations, the amount of SN is at least 2.0 wt % of the total liquid electrolyte. In some variations, the amount of SN is at least 2.5 wt % of the total liquid electrolyte. In some variations, the amount of SN is at least 3.0 wt % of the total liquid electrolyte. In some variations, the amount of SN is at least 3.5 wt % of the total liquid electrolyte. In some variations, the amount of SN is at least 4.0 wt % of the total liquid electrolyte. In some variations, the amount of SN is at least 4.5 wt % of the total liquid electrolyte. In some variations, the amount of SN is at least 5.0 wt % of the total liquid electrolyte.

[0085] In some variations, the amount of SN is less than or equal to 6.0 wt % of the total liquid electrolyte. In some variations, the amount of SN is less than or equal to 5.5 wt % of the total liquid electrolyte. In some variations, the amount of SN is less than or equal to 5.0 wt % of the total liquid electrolyte. In some variations, the amount of SN is less than or equal to 4.5 wt % of the total liquid electrolyte. In some variations, the amount of SN is less than or equal to 4.0 wt % of the total liquid electrolyte. In some variations, the amount of SN is less than or equal to 3.5 wt % of the total liquid electrolyte. In some variations, the amount of SN is less than or equal to 3.0 wt % of the total liquid electrolyte. In some variations, the amount of SN is less than or equal to 2.5 wt % of the total liquid electrolyte. In some variations, the amount of SN is less than or equal to 2.0 wt % of the total liquid electrolyte. In some variations, the amount of SN is less than or equal to 1.5 wt % of the total liquid electrolyte. In some variations, the amount of SN is less than or equal to 1.0 wt % of the total liquid electrolyte.

[0086] In some variations, the amount of HTCN is at least 0.01 wt % of the total liquid electrolyte. In some variations, the amount of HTCN is at least 0.1 wt % of the total liquid electrolyte. In some variations, the amount of HTCN is at least 0.5 wt % of the total liquid electrolyte. In some variations, the amount of HTCN is at least 1.0 wt % of the total liquid electrolyte. In some variations, the amount of HTCN is at least 1.5 wt % of the total liquid electrolyte. In some variations, the amount of HTCN is at least 2.0 wt % of the total liquid electrolyte. In some variations, the amount of HTCN is at least 2.5 wt % of the total liquid electrolyte. In some variations, the amount of HTCN is at least 3.0 wt % of the total liquid electrolyte. In some variations, the amount of HTCN is at least 3.5 wt % of the total liquid electrolyte. In some variations, the amount of HTCN is at least 4.0 wt % of the total liquid electrolyte. In some variations, the amount of HTCN is at least 4.5 wt % of the total liquid electrolyte. In some variations, the amount of HTCN is at least 5.0 wt % of the total liquid electrolyte. In some variations, the amount of HTCN is at least 5.5 wt % of the total liquid electrolyte.

[0087] In some variations, the amount of HTCN is less than or equal to 6.0 wt % of the total liquid electrolyte. In some variations, the amount of HTCN is less than or equal to 5.5 wt % of the total liquid electrolyte. In some variations, the amount of HTCN is less than or equal to 5.0 wt % of the total liquid electrolyte. In some variations, the amount of HTCN is less than or equal to 4.5 wt % of the total liquid electrolyte. In some variations, the amount of HTCN is less than or equal to 4.0 wt % of the total liquid electrolyte. In some variations, the amount of HTCN is less than or equal to 3.5 wt % of the total liquid electrolyte. In some variations, the amount of HTCN is less than or equal to 3.0 wt % of the total liquid electrolyte. In some variations, the amount of HTCN is less than or equal to 2.5 wt % of the total liquid electrolyte. In some variations, the amount of HTCN is less than or equal to 2.0 wt % of the total liquid electrolyte. In some variations, the amount of HTCN is less than or equal to 1.5 wt % of the total liquid electrolyte. In some variations, the amount of HTCN is less than or equal to 1.0 wt % of the total liquid electrolyte.

[0088] The electrolyte solvent may also have a salt dissolved therein. The salt may be any type of salt suitable for use in a battery cell. For example, but not limitation, salts used in lithium-ion battery cells include LiPF6, LiBF4, LiClO4, LiSO3CF3, LiN(SO2CF3)2, LiBC4O8, Li[PF3(C2CF5)3], and LiC(SO2CF3)3. Other salts are also possible, including combinations of salts.

[0089] The liquid electrolytes described herein may be valuable in battery cells, including those used in electronic devices and consumer electronics. An electronic device herein may refer to any electronic device known in the art. For example, an electronic device may be a telephone such as a mobile phone and a landline phone, or any communication device such as a smart phone (including, for example, ), and email sending / receiving devices. The electronic device may also be an entertainment device, including a portable DVD player, a conventional DVD player, a Blu-ray player, a video game controller, a music player such as a portable music player (e.g., ). The electronic device may be part of a display such as a digital display, a television monitor, an e-book reader, a portable web browser (e.g., ), a watch (e.g., Apple Watch), or a computer monitor. The electronic device may also be part of a device that provides control, such as controlling the flow of images, video, sound (e.g., Apple ), or it may be a remote control for an electronic device. In addition, the electronic device may be a part of a computer or its accessories, such as a hard drive tower housing or protective case, a laptop housing, a laptop keyboard, a laptop trackpad, a desktop computer keyboard, a mouse, and a speaker. The anode unit, lithium metal battery, and battery pack may also be applied to devices such as watches or clocks.

[0090] For the purpose of illustration, the foregoing description uses specific nomenclature to provide a thorough understanding of the embodiments. However, it will be apparent to those skilled in the art that specific details are not required in order to practice the embodiments. Therefore, for the purpose of illustration and description, the foregoing description of the specific embodiments described herein is presented. They are not intended to be exhaustive or to limit the embodiments to the disclosed precise forms. It will be apparent to those of ordinary skill in the art that, in view of the above teachings, many modifications and variations are feasible.

Claims

1. A liquid electrolyte comprising a bis(2,2,2-trifluoroethyl)carbonate (TFEC) diluent and a bis(1,1-difluoroethoxy)ethane (BDOE) solvent.

2. The liquid electrolyte of claim 1, wherein the ratio of wt% TFEC diluent to wt% BDOE solvent can be 1:5.0-1:2.

0.

3. The liquid electrolyte according to claim 1, wherein the liquid electrolyte comprises a lithium salt selected from the group consisting of LiFSI, LiTFSI, LiBOB, LiPF6, LiBF4, LiClO4, LiSO3CF3, LiN(SO2F)2, LiN(SO2CF3)2, LiBC4O8, Li[PF3(C2CF5)3], LiC(SO2CF3)3 and combinations thereof.

4. The liquid electrolyte according to claim 3, wherein the lithium salt comprises LiFSI.

5. The liquid electrolyte according to claim 3, wherein the lithium salt comprises LiFSI and LiBOB. 6 . The liquid electrolyte according to claim 3 , wherein the amount of the lithium salt is 15 mol % to 50 mol % of the liquid electrolyte.

7. The liquid electrolyte according to claim 1, comprising an additive selected from the group consisting of N-methyl-N-propylpyrrolidinium bis(fluorosulfonyl)imide, lithium difluoro(oxalato)borate (LiDFOB), prop-1-ene-1,3-sultone (PES), methylene methanedisulfonate (MMDS), propylene carbonate (PC), vinyl ethylene carbonate (VEC), propane sultone (PS), fluoroethylene carbonate (FEC), succinonitrile (SN), ethylene carbonate (VC), adiponitrile (ADN), ethylene glycol bis(2-cyanoethyl) ether (EGPN), and combinations thereof.

8. A battery cell, comprising: a cathode comprising a cathode active material disposed on a cathode current collector; an anode comprising an anode active material disposed on an anode current collector, the anode being oriented toward the cathode such that the anode active material faces the cathode active material; a separator disposed between the cathode active material and the anode active material; and The liquid electrolyte according to claim 1, wherein the liquid electrolyte is disposed between the cathode and the anode.

9. The battery cell of claim 8, the battery cell having an external operating pressure of 20 psi or less. 10 . The battery cell of claim 8 , comprising a polymer composite layer disposed between the anode and the separator.

11. The battery cell of claim 10, wherein the polymer composite layer has a porosity of less than 10.0%. 12 . The battery cell of claim 10 , comprising an anode cap layer disposed between the anode and the polymer composite layer.

13. The battery cell of claim 12, wherein the anode cap layer is selected from Sn, Cu, and combinations thereof.

14. The battery cell of claim 10, wherein the polymer composite layer adheres the anode cap layer to the separator. 15 . The battery cell of claim 10 , wherein the polymer composite layer comprises a cross-linked polymer backbone, polyethylene glycol, polycaprolactone, and a lithium salt.

16. The battery cell of claim 15, wherein the cross-linked polymer backbone has an uncross-linked molecular weight between 100,000 g / mol and 2,000,000 g / mol and is selected from the group consisting of PVDF-HFP, PEGDMA, poly-DDA, PVB, PUA, PEO, PAN, PMMA, and copolymers thereof.

17. The battery cell of claim 15, wherein the polyethylene glycol has a molecular weight between 20,000 g / mol and 200,000 g / mol and comprises between 1.0 wt% and 20.0 wt% of the polymer composite layer.

18. The battery cell of claim 15, wherein the polycaprolactone has a molecular weight between 20,000 g / mol and 200,000 g / mol and comprises between 1.0 wt% and 40.0 wt% of the polymer composite layer.

19. The battery cell of claim 15, wherein the ratio of one or more lithium salts to the sum of the cross-linked polymer backbone, the polyethylene glycol, and the polycaprolactone is less than 0.4:1.

0.

20. The battery cell of claim 15, wherein the cross-linked polymer backbone is PVDF-HFP.

Citation Information

Patent Citations

  • Oxide mixture and complex oxide coatings for cathode materials

    US11695108B2

  • Aluminum-doped lithium cobalt manganese oxide batteries

    US11757096B2

  • High voltage, high volumetric energy density li-ion battery using advanced cathode materials

    US20140272563A1

  • Cathode active materials for lithium-ion batteries

    US20170263917A1

  • Cathode active materials for lithium-ion batteries

    US20170263928A1